(untitled) (Research, Society and Development, 2021)
Introduction: Health as an inherent right to citizenship in the 1988 constitution of Brazil was a conquest by social groups who, at the time, dissatisfied with inequalities and exclusion of part of the population to health services, fought to consolidate the Unified Health System (SUS). Through this conquest, public policies were implemented to guarantee this right. However, unequal access to health services is still a problem which hinders the effective exercise of SUS due to the barriers found in various aspects, such as structural, operational and relational. Objective: Review of scientific production on accessibility to SUS dental services was performed, characterizing the main barriers to access. Method: Integrative literature review with search of articles published between 2010 and 2017 was carried out on the Scientific Electronic Library Online (SciELO) and Latin American and Caribbean literature on Health Sciences (LILACS) databases, using the following keywords: “access”, “accessibility”, “dental services” and “oral health”. Results: A total of 24 articles were selected, presenting as main barriers to access the lack of information about services and the importance of oral health, self-assessment of oral health, the lack of materials, human resources and supplies, the failure to implement current public policies, among others. Conclusion: Overcoming these barriers to access is fundamental in order to diminish social inequities and to promote social justice, as well as new studies aimed at the groups considered most vulnerable.